The Effect of Personal Profile Information and Message Valence on Information Credibility and Purchase Intentions in Travel-Related Consumer-Generated Media - Guan, L. (2013)
With an increasing number of travellers searching for information in travel-related consumer-generated media (CGM), the credibility of information has become a central concern. This study examines the impact of personal profile information (PPI) and information valence on consumers’ perception of information credibility and purchase intentions. A scenario-based role-playing experiment was conducted to explore this research topic. Findings show that information with PPI will positively affect information credibility compared with anonymous information, while its impact on purchase intentions is not significant. An interesting finding indicates information credibility will not positively influence purchase intentions. There exists significant differences in purchase intentions between positive and negative information, while the difference in information credibility is not significant. With respect to the interaction effect, the difference in information credibility and purchase intentions between positive and negative information is obvious for information with PPI, while for anonymous information, the difference only exists in purchase intentions. For positive information, information with PPI and anonymous information has a significantly different effect on information credibility and purchase intentions, while for negative information, the presence of PPI only has an effect on information credibility. Findings in this study also verify that positive information with PPI is perceived as more credible than other types of information. Findings of this study seem to have some theoretical implications and in turn can make contributions to actual managerial practice.